Earnings Management To Sustain Consecutive Earnings Increases - Na, Kyunga (Journal of Applied Business Research, 2017)
In this paper, I examine the pattern of earnings management undertaken by firms with a string of at least five-year consecutive earnings increases. Results indicate that discretionary accruals of those firms intensify as firms move towards the end of an earnings string while the extent of discretionary accruals declines sharply when the string ends.
Keywords: Earnings Management; Discretionary Accruals; Consecutive Earnings Increases; Earnings String